Reducing the provincial poverty rate in Indonesia: The impact of local government expenditure - Nurias, Nurias; Johari, Sobar M; Muljarijadi, Bagja; Wardhana, Adhitya (Jurnal Ekonomi & Studi Pembangunan, 2023)
This study seeks to examine the effect of local government expenditure on the improvement of provincial welfare in Indonesia. It is necessary to increase public capital such as basic infrastructure and public facilities, as well as to improve public services such as health, education, and social protection. Based on previous studies, research on government spending on poverty has a significant effect on poverty reduction, but some other studies are not the case, namely government spending has not been significant in reducing poverty and improving welfare. The data used in government expenditure is expenditure based on functions, particularly health, education, and social protection functions in the province, both district/city and provincial government expenditures obtained from the Directorate General of Financial Balance (DJPK), while the provincial poverty rate serves as a proxy for regional welfare. Over the period 2015-2021, the Fixed Effect model using the Generalized Least Square Estimation (GLSE) approach is used to estimate outcomes for 34 provinces in Indonesia. The results indicated that government expenditure on the health sector and education sector had a negative significant influence on reducing the poverty rate, whereas government expenditure on social protection did not. The control factors, such as economic growth, had a negative effect on poverty reduction in Indonesia, whereas the unemployment rate and informal labor in the agricultural sector had positive and significant effects. Government policies, especially government spending, have contributed well to reducing poverty, but the government should pay attention to the integration of spending programs with other programs.